Themis differentially regulates T follicular helper cell differentiation during early and late stages of chronic viral infection - Zhu, Yuzhen; Bao, Yuzhou; Wang, Ning; Gan, Qifeng; Tang, Jian; Cong, Yu; Hou, Bowen; Quan, Minxue; Yan, Chaonan; Liu, Siyi; Lin, Shuo; Zhang, Xiaobin; et al. (Frontiers in Immunology, 2025)
IntroductionT follicular helper (TFH) cells are critical for humoral immunity during chronic viral infection, but the mechanisms guiding their differentiation from a novel CD4⁺ T cell progenitors remain incompletely understood. Themis, a T cell-specific adaptor protein, has been implicated in T cell development and function, but its role in peripheral CD4⁺ T cell differentiation under chronic antigen stimulation has not been defined.MethodsWe used a chronic lymphocytic choriomeningitis virus (LCMV) Clone13 infection model in wild-type and Themis conditional knockout (cKO) mice. A combination of adoptive cell transfer, flow cytometry, histological analysis, and single-cell RNA sequencing (scRNA-seq) was applied to analyze the differentiation of CD4⁺ T cells into TFH cells at multiple infection stages.ResultsThemis expression is strongly upregulated in TFH cells at early stages of infection, and as expected, Themis promotes TFH cell differentiation at this stage. However, unexpectedly, at the late stages of chronic LCMV infection, Themis-deficient CD4+ T cells favored TFH cell differentiation and helped control the virus by enhancing GC responses and antibody production, suggesting that Themis inhibits TFH cell differentiation at this stage. In the late stage we found that Themis inhibits the differentiation of CD4+ T cell progenitors into TFH cells through transcriptional regulation.DiscussionOur study uncovers a dual-stage regulatory role of Themis in TFH cell differentiation during chronic viral infection. While promoting TFH generation early, Themis unexpectedly restrains excessive differentiation at later stages, suggesting its function is context- and time-dependent. These findings highlight Themis as a key temporal regulator of CD4⁺ T cell fate decisions under chronic antigenic stress.